Implementasi Kegiatan Sosialisasi dan Rembuk Stunting di Desa Utama Kecamatan Cijeungjing Kabupaten Ciamis - Syahrul Apriansyah; Rahma Aulia Kharisma; Rizka Nurlela; Elnia Nur Aziza; Kiki Endah (CV SWA Anugerah, 2024)
Implementation of Socialization and Stunt Stunts Activities in the main villages of Utama Discomfort Cijeungjing District Ciamis. the implementation of this activity uses the material exposure method. The main objective is to focus on dealing with stunting issues that are at the heart of improving the public health of the Main Villages Utama. And in this way we need a holistic approach that involves health education, easy access to medical services, as well as a healthy lifestyle for pregnant mothers and babies as stunting prevention. This government-society collaboration is a government program in the fight against and towards zero stunting in order to be a significant outcome in dealing with health problems and for health to improve in the future generations